What influences the surgeon’s decision between anatomical and reverse total shoulder arthroplasty in primary osteoarthritis? A case-vignette study - Dries Boulidam; Arno A. Macken; Tim Kraal; Tjarco D. W. Alta; Michel P. J. van den Bekerom; Laurent Lafosse; Thibault Lafosse; Geert A. Buijze (Journal of Orthopaedics and Traumatology)
Abstract Background Historically, anatomical total shoulder arthroplasty (ATSA) has been the standard intervention for primary osteoarthritis in patients with an intact rotator cuff. However, there is an increasing trend towards utilizing reverse total shoulder arthroplasty (RTSA) as an alternative in specific cases. The aim of this study is to investigate the influence of the degree of retroversion, percentage of subluxation and age on the surgeon’s decision-making in the choice between ATSA and RTSA in patients with primary osteoarthritis with an intact rotator cuff. Methods Attendees of a large international congress on (live) shoulder surgery were requested to complete a questionnaire consisting of closed and open questions regarding shoulder arthroplasty and clinical scenarios. Participants were divided into high- and low-volume surgeons (< 30 cases per year). Results A total of 166 responses were collected. In total, 37 different nationalities from all six continents were represented among the respondents. The included participants had a median experience of 11 years (interquartile range, IQR: 6–18). In total, 56 (39%) participants were considered high-volume surgeons. The median degree of retroversion, the median percentage of posterior subluxation and the median age for which participants still considered performing ATSA rather than RTSA were respectively 20° (IQR: 10–20.75), 70% (IQR: 60–80) and 70 years (IQR: 65–75). Furthermore, a low degree of consensus was observed for the choice of treatment in the ten case vignettes with these factors combined. In case of significant disagreement, RTSA was preferred more often by high-volume surgeons compared with low-volume surgeons. Conclusions This case-vignette study highlights that the degree of retroversion, percentage of subluxation of the humeral head and the patient’s age are important factors to consider in the surgeon’s decision-making between ATSA and RTSA. However, our findings indicate limited consensus among orthopaedic surgeons concerning the precise impact of these patient-specific factors. Despite the lack of consensus, some trends can be identified. Overall, participants preferred treatment with RTSA in patients with a high degree of retroversion and older age. Treatment with ATSA was preferred in patients with a younger age, without severe glenoid retroversion and a posterior subluxation of < 80%. The level of evidence is Level V, expert opinion.